2018
DOI: 10.1007/s11249-018-1048-4
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Material Transfer in Friction Between Metals: Initial Phenomena and Effects of Roughness and Boundary Lubrication in Sliding Between Aluminium and Tool Steels

Abstract: In the absence of a lubricant, the friction we measure in sliding contact between metals is typically high and quite erratic, with rapid fluctuations. If we filter out these rapid fluctuations, we can typically also notice slower trends, which can lead to quite dramatic friction changes. Unless careful studies are performed, the cause to this behaviour cannot be understood. How come a material couple cannot be characterised with a specific coefficient of friction? The present paper sets out to add understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Steel ring material has obviously shown superiority in having less friction with TWA aluminum cylinder liner compared to the two other materials, cast iron ring and ductile iron plasma molly faced ring. The surface of steel gives the overall friction among these materials, this was investigated by Viktoria Westlund et al [20] which concluded that smooth sliding surfaces were consistently and strongly related to low sliding friction. The results of our study have showed that ductile iron is still better choice for friction than cast iron.…”
Section: Discussionmentioning
confidence: 99%
“…Steel ring material has obviously shown superiority in having less friction with TWA aluminum cylinder liner compared to the two other materials, cast iron ring and ductile iron plasma molly faced ring. The surface of steel gives the overall friction among these materials, this was investigated by Viktoria Westlund et al [20] which concluded that smooth sliding surfaces were consistently and strongly related to low sliding friction. The results of our study have showed that ductile iron is still better choice for friction than cast iron.…”
Section: Discussionmentioning
confidence: 99%
“…5(a) that the surface hardness of aluminium alloys is significantly less than that of tool steel. The plastic deformation of aluminium pin tip gradually increases with the increase of sliding distance s u [17]. The scratches during the friction process cause the aluminium alloy detachment from surface, which is easy to adhere to tool (Fig.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Aluminium chips are easy to adhere to die surface. Accompanied by the oxidation reaction that might occur, a transfer layer with complex compositions will be formed [17]. Because of the significant adhesion between the die and the aluminium alloy sheet, the AADD system has unique friction characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the researchers (Wang et al , 2010; Westlund et al , 2018) have studied the wear and friction characteristics of aluminium alloys by considering steel as a counter-face material, having a flat on flat contact configuration, during the experiments. Few researchers (Dewan and Mohammad, 2012; Pan et al , 2018; Srinivasula Reddy and Kaliveeran, 2019a) focused on the friction behaviour of aluminium-to-aluminium metal alloy during full sliding.…”
Section: Introductionmentioning
confidence: 99%